TRAINING IN PHYSICAL EDUCATION FOR INTERVENTION IN MENTAL HEALTH (Fiep Bulletin - online, 2013)
This work had as objective the investigation of training in Physical Education for intervention in the mental health field. Thinking about the increasing more and more effective participation of physical education in this area, this research had as general objective to identify the core competencies necessary for the physical education professional to work in the mental health field. And as specific objectives: to get to know the approach to mental health / illness; to understand the work that is done with mental health patients by physical education professionals, to identify the skills to work in the mental health field and check what active professionals think of the training and whether training in physical education addresses the subject. Training in Physical Education and the activities conducted in the area of mental health in psychiatric institutions and issues on public and collective health are concepts that underlie this work. The methodology used was qualitative. The survey was conducted through semi-structured interviews with workers in the mental health team where they work. Through the speeches were created units of meaning. The data were categorized, analyzed and based on discussion with the specialized literature, we constructed three categories: concepts and definitions of mental health, the work of the physical education professional in mental health and their skills and training in physical education and mental health. The studied group was found to be knowledgeable of the issues that guide the work on mental health and, in general brought in theirs speech homogeneous responses. The analysis identified that the knowledge of existing conditions, the appropriation of public health policies (SUS), and its understanding, appear as essential skills for this professional, and that they were not present in their initial training.
Keywords: Formation; Physical Education; Mental Health